FINANCE REFLECTED BY FUNHOUSE MIRRORS: A PROPOSAL OF INDIRECT REGULATION (GATEKEEPERS) TO CRYPTO CENTRALIZED EXCHANGES (CEX) - de Oliveira Rosa, Marcus Paulus; Caminha, Lucas (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2023)
Money is money, securities are securities, and banking is banking. Their fundamentals are not changed by whether technology rails are centralized (classic) or pseudo-decentralized (virtual assets) – the song remains the same. As such, this paper does not reinvent the wheel on why we should regulate cryptoasset centralized exchanges (CEXs), as there is enough bibliography from today to the XVII century to go around on that. Instead, we focus on how to regulate the CEXs, which comes into play in a world where their distributed ledger technology (DLT) rails are off-the-grid and hinder regulators from: (i) collecting market data (information asymmetry); and (ii) practical enforcement (technology/operational asymmetry). After revising current regulatory practices from various countries, we identify grounds for a practical approach – we propose that regulators might enforce full trading/financial intermediation obligations on the CEXs by enacting an indirect regulation/gatekeeper scheme, as inspired by the U.S. Foreign Account Tax Compliance Act (FATCA). In this model, regulators would restrict traditional institutions (i.e., banks, broker-dealers, clearings, funds) from transacting with CEXs which do not provide adequate evidence of material compliance with their trading/financial intermediation obligations. On a final remark, we narrate a growing movement which aims to insulate non-compliant crypto from the financial systems altogether, avoiding risks of contagion.